Programa Bolsa Família: o perfil das famílias desligadas voluntariamente no município de Miranorte – TO no ano de 2019 - Silva, Lidielly Andrade Cabal (Universidade Federal do Tocantins, 2024)
This research aimed to analyze the Bolsa Família Program: the profile of voluntarily disconnected families in the municipality of Miranorte – TO in 2019, based on data collected in the Single Registry database, in the printed forms where these families respond to the standard questionnaires for insertion in the social programs of the Federal Government, as well as for the withdrawal of the Bolsa Família Program. This research has as methodology a bibliographical study, and documental analysis, in which its theoretical basis is based on Marx's social theory. The results indicate that, in relation to the termination forms, it is clear that they mask reality, as the research found that there is only one form for voluntary terminations. And from the moment the families sign this term, it is not known whether this family left voluntarily or guided, and among them there may be a family that was instructed to leave.